The prognostic significance of CXCR4 and SDF-1 in differentiated thyroid cancer depends on CD8+ density - Alexander Wilhelm; Isabelle Lemmenmeier; Alexandros Lalos; Alberto Posabella; Venkatesh Kancherla; Salvatore Piscuoglio; Tarik Delko; Markus von Flüe; Kathrin Glatz; Raoul André Droeser (BMC Endocrine Disorders, 2022)
Abstract Background Tumor infiltration with cytotoxic CD8+ T-cells is associated with a favorable outcome in several neoplasms, including thyroid cancer. The chemokine axis CXCR4/SDF-1 correlates with more aggressive tumors, but little is known concerning the prognostic relevance in relation to the tumor immune microenvironment of differentiated thyroid cancer (DTC). Methods A tissue microarray (TMA) of 37 tumor specimens of primary DTC was analyzed by immunohistochemistry (IHC) for the expression of CD8+, CXCR4, phosphorylated CXCR4 and SDF-1. A survival analysis was performed on a larger collective (n = 456) at RNA level using data from The Cancer Genome Atlas (TCGA) papillary thyroid cancer cohort. Results Among the 37 patients in the TMA-cohort, the density of CD8+ was higher in patients with less advanced primary tumors (median cells/TMA-punch: 12.5 (IQR: 6.5, 12.5) in T1–2 tumors vs. 5 (IQR: 3, 8) in T3–4 tumors, p = 0.05). In the TCGA-cohort, CXCR4 expression was higher in patients with cervical lymph node metastasis compared to N0 or Nx stage (CXCR4high/low 116/78 vs. 97/116 vs. 14/35, respectively, p = 0.001). Spearman’s correlation analysis of the TMA-cohort demonstrated that SDF-1 was significantly correlated with CXCR4 (r = 0.4, p = 0.01) and pCXCR4 (r = 0.5, p = 0.002). In the TCGA-cohort, density of CD8+ correlated with CXCR4 and SDF-1 expression (r = 0.58, p < 0.001; r = 0.4, p < 0.001). The combined marker analysis of the TCGA cohort demonstrated that high expression of both, CXCR4 and SDF-1 was associated with reduced overall survival in the CD8 negative TCGA cohort (p = 0.004). Conclusion These findings suggest that the prognostic significance of CXCR4 and SDF-1 in differentiated thyroid cancer depends on the density of CD8 positive T-lymphocytes. Further studies with larger sample sizes are needed to support our findings and inform future investigations of new treatment and diagnostic options for a more personalized approach for patients with differentiated thyroid cancer.